Pengaruh Kepemimpinan Dan Komitmen Organisasi Terhadap Kompetensi Kerja Karyawan Pt. Mega Wisata Tour & Travel - Angelai Rena; Syawaluddin Syawaluddin; Mila Asmawiani Okta; Thomas Sumarsan Goh (STIE AMKOP, 2022)
This research was conducted on employees who work at PT. Mega Wisata Tour & Travel. The purpose of this study was to determine and analyze the effect of leadership and organizational commitment on employee work competencies. The population and sample in this study were found to be 32 people. The sampling technique used is saturated. Data collection techniques are by distributing questionnaires and interviews. Data analysis used multiple linear regression analysis. The conclusion in the study that simultaneously leadership and organizational commitment have a positive and significant effect on the work competence of employees of PT. Mega Wisata Tour & Travel. Partially, leadership has a positive and significant effect on the work competence of employees of PT. Mega Wisata Tour & Travel. Partially, organizational commitment has a positive and significant effect on the work competence of employees of PT. Mega Wisata Tour & Travel. The magnitude of the coefficient of determination can be seen from the value of Adjusted R Square is: 0.265 means Leadership and Organizational Commitment is able to explain employee competence by 26.5% while the remaining 73.5% is determined by variables that are not studied such as: Training, Job Performance, Career Development, and etc. Keywords: Leadership, Organizational Commitment, and Employee Work Competence